Relationship Between Breast Milk Feeding and COVID-19 Incidence in Children Aged 0-2 Years at Siloam Hospital Kelapa Dua During The Pandemic - Setiawan, Jovanicha P.; Rivami, Dwi Savitri (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: The COVID-19 pandemic has claimed more than 6 million lives worldwide, and children are not spared from its danger. Breast milk is known to protect babies from various kinds of infections. Until now there are few data regarding the relationship between breastfeeding and the incidence of COVID-19 in children aged 0-2 years in Indonesia. This study aims to further examine the relationship between breastfeeding and the incidence of COVID-19 in children aged 0-2 years. Siloam Hospitals Kelapa Dua (SHKD) was chosen as a location because it was one of the referral hospitals for treating COVID-19 for pediatric patients in Tangerang that can be accessed by the researcher.Methods: This study was conducted using a cross-sectional study method on a sample of children aged 0-2 years from the medical record database of Siloam Hospitals Kelapa Dua for the period 2020 to 2022.Result: Upon calculation, it was found that the p-value is 0,154 (p>0,05). From 61 sample, 37,7% of the samples were breastfed and 44,3% was COVID-19 positive.Conclusions: No significant relationship was found between breastfeeding and COVID-19 infection among children aged 0-2 years old in SHKD.